PEMIKIRAN FUKUZAWA YUKICHI MENGENAI MODERNISASI JEPANG - Intan Anggi Nanda Sari; Prof. Dr. Isjoni, M.Si2 '; Drs. Kamaruddin, M.Si ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study was to describe the condition of Japan during the Tokugawa shogunate, to know what IS the background of the Meiji Restoration, analyzed the thinking of Fukuzawa Yukichi on the modernization of Japan, to know the development of education in Japan, knowing the cultural development in Japan and determine the effect of Fukuzawa Yukichi’s thought against Japan modernization. The method used in this research is descriptive method of historical research, a method that discuss several possibilities to solve actual problems with the way collect data, organize or classify, analyze, and interpret. The study concluded that Fukuzawa Yukichi thinking about modernization in Japan dilator background by the desire to make Japan as a free and independent country in the world. Fukuzawa Yukichi thought about the modernization of education is: a. Datsu A Ron (out of Asia). The most important target is "the pursuit of surpassing Western countries". In an effort to follow the example of the Japanese Western countries so as to expand and colonize neighboring countries before World War II. Fukuzawa idea was used by the military government which intends to build a "Neighborhood East Asia Co-Prosperity". The idea of the famous blaze in his book entitled "Gakumon no susume". Fukuzawa wrote "As the most powerful way to achieve the country's goal is through education because God does not put another human being". Thought Fukuzawa Yukichi that became a cornerstone in the development of culture in Japan are: cultural changes done in Japan should start from the local values deemed superior, applying mental Bushido or way of life samurai (hard working, honest, follow the leader, not individualistic, not selfish, responsible, clean heart, to be shameless). In Western culture we can all apply in our daily lives but traditional Japanese culture should still be upheld as the hallmark and foundation of life of Japanese society. Western culture is just as a comparison.Key Words: Fukuzawa, Thought, Modernization, Japan